Algunas Experiencias Que Han Contribuido A Mejorar El Proceso De Enseñanza-Aprendizaje De Las Matemáticas (2019)
This article presents classroom experiences which have been implemented in some math courses that are taught at Universidad Tecnológica de Pereira, whose theoretical approach is the Learning Developer. For this work some methodological practices have been considered: Students´ background when they take any subject, these are valuable experiences at the time of introducing a new knowledge. The relation between mathematics and daily life. The importance of mathematics as a theoretical support in scientific and technological developments and their historical evolution and human cultural creation that has allowed the emergence and progress in different mathematical areas and knowledge. These experiences are the result of the research project: “Methodological Practices to improve the Linear Algebra Teaching and Learning, involving new Information and Communication Technologies”.